1997
DOI: 10.1177/019251397018002001
|View full text |Cite
|
Sign up to set email alerts
|

Guilt, Shame, and Family Socialization

Abstract: In this study, we argue for the importance of guilt and shame for the process of socialization via the role of these reflexive emotions in individuals' conformity to moral and social norms. Working from the assumption that the self-concept is the basis for feelings of guilt and shame, we test a number of hypotheses connecting the experience of these emotions to 3 styles of parental control (inductive, affective, and coercive). Undergraduate students ( N = 270) completed questionnaires designed to assess their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Such feelings of pride and guilt reflect a sense of duty or obligation to tip that stems from the internalization of tipping norms. Psychologists and sociologists have theorized and empirically demonstrated that processes of social learning and social identification often lead people to accept the appropriateness and legitimacy of social norms and to feel pride when complying with those norms and/or feel guilt and shame when violating them (Abell & Gecas, 1997;Richters & Waters, 1991). These internal rewards and sanctions motivate compliance with social norms even in the absence of external rewards and sanctions (Horne, 2003;Kerr, Garst, Lewandowski, & Harris, 1997).…”
Section: Sense Of Duty or Obligation To Tipmentioning
confidence: 99%
“…Such feelings of pride and guilt reflect a sense of duty or obligation to tip that stems from the internalization of tipping norms. Psychologists and sociologists have theorized and empirically demonstrated that processes of social learning and social identification often lead people to accept the appropriateness and legitimacy of social norms and to feel pride when complying with those norms and/or feel guilt and shame when violating them (Abell & Gecas, 1997;Richters & Waters, 1991). These internal rewards and sanctions motivate compliance with social norms even in the absence of external rewards and sanctions (Horne, 2003;Kerr, Garst, Lewandowski, & Harris, 1997).…”
Section: Sense Of Duty or Obligation To Tipmentioning
confidence: 99%
“…Social bonds, moral beliefs, and moral emotions are key mediators that are stressed in control theories. The development of moral beliefs and moral emotions of shame and guilt emerge during the process of primary socialization, and the family is essential for the development of these emotions (e.g., Abell & Gecas, 1997;Elster, 2007). The secondary socialization through school and the peer group may consolidate or adjust these emotions (e.g., Elkin & Handel, 1989;Gecas, 2000).…”
Section: Social Bonds Moral Beliefs and Emotions And Peer Exposure mentioning
confidence: 99%
“…9,13 However, the manner in which adolescents' cope with the impact of having a sibling with severe disabilities seems to be contradictory. On the one hand, active forms of adolescent coping are associated with an optimal family atmosphere combining closeness and individual autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…This input may contribute to the siblings experiencing problems in gaining positive self-esteem and self-confidence. 13 Some siblings of children with disabilities experience a sense of loneliness and isolation. In addition to the reactions of peers and others, these feelings are influenced by the appearance and behaviour of the child with a disability.…”
Section: Introductionmentioning
confidence: 99%